A comparative study of efficacy and safety of combination of indacaterol and tiotropium versus formoterol and budesonide in moderate to severe COPD - Bende, Manohar M.; Dudhgaonkar, Sujata; Jagdhani, Raviraj S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: COPD patients suffer persistent airflow obstruction and exacerbation despite treatment with LABA and ICS. Presently LABA+LAMA is least tested combination hence we want to compare efficacy and safety of combination of indacaterol and tiotropium versus formoterol and budesonide in moderate to severe COPD. Methods: This was an open labelled, parallel group trial involving 60 patients. of moderate to severe COPD having baseline postbronchodilator FEV1 ≥30% predicted and less than 80% predicted already on some kind of COPD treatment were included and, efficacy on lung function (FEV1) and safety in two groups, indacaterol+tiotropium once daily dpi versus formoterol+budesonide twice daily bd dpi were testedi24 hours postdose (trough) DPI in symptomatic patients of COPD of moderate to severe grade. Statistical analysis was done using repeated measures of ANOVA followed by Turkeys test. P value less than 0.05 were considered statistically significant. Results: Patient with baseline/post bronchodilator FEV1 ≥30% predicted and less than 80% predicted were included. The mean age was 55±5 years. At 4 weeks mean±SEM in peak FEV1 in indacaterol+tiotropium was 85.77±4.002 and in formoterol+budesonide was 77.33±5.598. At 12 weeks, mean ±SEM in peak FEV1 in indacaterol+tiotropium was 112.30±4.69 and formoterol+budesonide was 103±6.35. At 24 weeks, mean ±SEM in peak FEV1 in indacaterol+tiotropium= 125.3±5.18 and formoterol+budesonide=112.7±5.89. Adverse events were less in indacaterol+tiotropium group. No serious adverse event occurred. Indacaterol+tiotropium once daily is efficacious and safe as compared to formoterol+budesonide twice daily with less exacerbation. Conclusions: In patients having poorly controlled COPD despite background therapy (LABA, etophylline+theophylline, etc.) the introduction of indacaterol+tiotropium once daily compared to formoterol+budesonide twice daily DPI significantly improved the FEV1 by sustained bronchodilation, decreased exacerbation and is safe. Further studies are needed to assess quality of life and cost analysis.